Thermochemical Analysis of Urea and Citric Acid-Fuelled Solution Combustion for Zinc-Based Nano Oxide Synthesis - Simmi; Dr. Verjesh Kumar Magotra; Dr. Shaveta Thakur (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The present study investigates the influence of fuel type and combustion parameters on the synthesis efficiency and material characteristics of zinc-based nano metal oxides via the solution combustion process (SCP). Urea and citric acid were employed as organic fuels to facilitate redox reactions with zinc nitrate serving as the oxidizer. The thermal behavior, combustion reaction kinetics, fuel-to-oxidizer ratios (Φ), and their impact on combustion temperature, product morphology, and phase purity were systematically analyzed. Characterization techniques including flame observation, XRD, SEM and UV-Vis spectroscopy were employed to evaluate crystallinity, particle size range of the synthesized nanoparticles, along with efficiency of fuels used for combustion process. Results indicate that fuel type significantly affects the combustion flame temperature and reaction exothermicity, thereby influencing the structural and morphological attributes of the final oxide product. Urea-based synthesis exhibited rapid combustion and smaller particle sizes, while citric acid yielded more homogeneous and porous structures. The study underscores the role of fuel chemistry in tailoring nanomaterial properties and optimizing energy efficiency in SCP-based synthesis routes.